Bridging the Efficiency Gap: Fully Bridged Dinuclear Cu(I)‐Complexes for Singlet Harvesting in High‐Efficiency OLEDs. (9th March 2015) - Volz, Daniel; Chen, Ying; Wallesch, Manuela; Liu, Rui; Fléchon, Charlotte; Zink, Daniel M.; Friedrichs, Jana; Flügge, Harald; Steininger, Ralph; Göttlicher, Jörg; Heske, Clemens; Weinhardt, Lothar; et al.
<x xml:space="preserve">Abstract</x> The substitution of rare metals such as iridium and platinum in light‐emitting materials is a key step to enable low‐cost mass‐production of organic light‐emitting diodes (OLEDs). Here, it is demonstrated that using a solution‐processed, fully bridged dinuclear Cu(I)‐complex can yield very high efficiencies. An optimized device gives a maximum external quantum efficiency of 23 ± 1% (73 ± 2 cd A−1). <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>